Development of a Composting Chamber for the Reduction of Nitrogen Loss in Poultry Litter - Ogunwande, Gbolabo Abidemi (2015)
The study was undertaken to develop a chicken litter composting chamber and investigate the effects of turning frequency (TF) and carbon to nitrogen (C:N) ratio on the loss of nitrogen (N) in chicken litter piles. This was with a view to producing good quality compost.